1999
DOI: 10.1038/13671
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic mechanical strain regulates the development of engineered smooth muscle tissue

Abstract: We show that the appropriate combinations of mechanical stimuli and polymeric scaffolds can enhance the mechanical properties of engineered tissues. The mechanical properties of tissues engineered from cells and polymer scaffolds are significantly lower than the native tissues they replace. We hypothesized that application of mechanical stimuli to engineered tissues would alter their mechanical properties. Smooth muscle tissue was engineered on two different polymeric scaffolds and subjected to cyclic mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
281
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 428 publications
(292 citation statements)
references
References 33 publications
9
281
1
Order By: Relevance
“…These improvements in material behavior with mechanical stimulation have been commonly reported for engineered tissues, and are attributed to improved collagen synthesis and organization [12,[23][24][25]. For example, Pins et al found that greater stretch of self-assembled collagen fibers resulted in both improved collagen fibril alignment as measured by TEM as well as higher tangential elastic moduli [25].…”
Section: Discussionmentioning
confidence: 97%
“…These improvements in material behavior with mechanical stimulation have been commonly reported for engineered tissues, and are attributed to improved collagen synthesis and organization [12,[23][24][25]. For example, Pins et al found that greater stretch of self-assembled collagen fibers resulted in both improved collagen fibril alignment as measured by TEM as well as higher tangential elastic moduli [25].…”
Section: Discussionmentioning
confidence: 97%
“…The mechanical properties of synthetic ECM, for example, will regulate the ability of cells to rearrange adhesion peptides presented from the material, 52 and through their control of cell proliferation will regulate transfection of adherent cell populations. 67 Externally applied mechanical signals will also regulate the response of cells to the synthetic ECM 68 and the release of growth factors and subsequent tissue formation. 69 …”
Section: Combining and Integrating Signalingmentioning
confidence: 99%
“…Furthermore, an increase in ultimate tensile strength and tissue stiffness is observed, compared to static control. 21,24,28,29,38,39 In a recently developed bioreactor concept, the Diastolic Pulse Duplicator (DPD), 25 dynamic strains were induced in the heart valve leaflets by applying a dynamic pressure difference over the closed valve. The strain-based conditioning approach was tested by culturing human heart valve leaflets in vitro.…”
Section: Introductionmentioning
confidence: 99%